Applying a Part of the Daily Dose as Boli May Improve Intrathecal Opioid Therapy in Patients With Chronic Pain. Issue 5 (9th February 2016) - Reck, Tim; Chang, En‐Chul; Béchir, Markus; Kallenbach, Ulrich
Abstract : Objectives: The speed of intrathecal drug administration (slow continuous infusion vs. rapid bolus application) might influence the efficacy of therapy despite the equal daily dose in both administration patterns. We tested this hypothesis in a small prospective single‐centre pilot study in a population of chronic pain patients with intrathecal opioid therapy. Methods: Ten patients receiving intrathecal opioids for chronic pain assessed their pain four times daily on a numeric rating scale (NRS), more than the time course of six weeks divided into three blocks of two weeks each: Baseline evaluation (intrathecal pumps with previously established continuous infusion settings), followed by two blinded trial blocks of continuous (same pump parameters as during evaluation) and bolus (40% of daily dose split into four equal boli applied every six hours, with the remaining 60% as background continuous infusion) regimes. Patients were randomized in a crossover fashion. Results: 6/10 patients reported significantly lower NRS‐scores during bolus as compared to continuous trial blocks while only one patient showed the opposite effect. Overall, bolus trial blocks were associated with a small but significant reduction of NRS‐scores (mean −0.56; p  < 0.0001). Side‐effects related to bolus infusions were not reported. Conclusions: Intermittent bolus administration may be helpful for increasing the efficacy of intrathecal opioid therapy of chronic pain.